PENGARUH INTERKONEKSI DISTRIBUTED GENERATION DALAM SISTEM DISTRIBUSI TENAGA LISTRIK PT. PLN (PERSERO) CABANG MANOKWARI - , Elias Kondorura Bawan ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Nowadays, new developments in electrical power generation technologies enable the electrical power to be generated by relatively small-scale power plants close to the consumption centers, i.e. directly connected to the distribution networks. This paper aims to investigate the impact of distributed generation on distribution system losses and voltage profile. The main objective is to reduce the power losses and to increase the voltage profile based on location of DG and size of injection. This paper also present economic analysis based on cost benefit analysis. Using application program ETAP 6.0 and the Manokwari electricity distribution system as case study, the results shows that at certain location, the power injection of DG has decrease the drop voltage from 14,48% to 6,34% and losses from 240,15 kW to 99,39 kW and more economic than without DG installation. The best location of interconnection is 80 km from power grid and injection of 85% DG capacity.